2010
DOI: 10.4314/sajas.v39i4.51128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of niacin supplementation on performance and blood parameters of Holstein cows

Abstract: In this experiment the response to niacin supplementation was evaluated. Twelve multiparous Holstein cows were used in a replicated 4 × 4 Latin square statistical model in four 24 d periods as replicates. At the onset all the cows were in early lactation with days in milk (DIM) at 60.1 ± 16.1 and an average milk yield of 31.4 ± 5.44 L/d. The treatments were: N0 -control (no niacin supplement); N1 -control + 12 g niacin/d; N2 -control + 14 g niacin/d and N3 -control + 16 g niacin/d. Means were compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…In our study, glucose concentrations were significantly higher in cows that received niacin compared to the control group during all the weeks of examination. Other authors (Doreau and Ottou 1996;Di Constanzo 1997;Ghorbani et al 2008;Karkoodi and Tamizrad 2009) have found similar results, i.e. cows that received niacin indicated elevated plasma glucose concentrations in comparison with the control group.…”
Section: Discussionmentioning
confidence: 53%
“…In our study, glucose concentrations were significantly higher in cows that received niacin compared to the control group during all the weeks of examination. Other authors (Doreau and Ottou 1996;Di Constanzo 1997;Ghorbani et al 2008;Karkoodi and Tamizrad 2009) have found similar results, i.e. cows that received niacin indicated elevated plasma glucose concentrations in comparison with the control group.…”
Section: Discussionmentioning
confidence: 53%
“…Only a few studies recorded increased glucose concentration (Ghorbani et al, 2008;Karkoodi & Tamizrad, 2009). In contrast, in the present trial the researchers found significantly lower plasma glucose concentrations in cows that were receiving supplemental niacin compared with those on the unsupplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…The similar condition is valid for milk parameters. Enhanced niacin concentrations in blood did not necessarily affect milk production or composition (Karkoodi et al, 2009).…”
Section: Sourcesmentioning
confidence: 85%
“…When animals have received deficient levels of tryptophan, increasing amounts of dietary tryptophan are used first to restore nitrogen balance, next to restore blood pyridine nucleotides and then to be excreted as niacin metabolites. Under starvation or energy restriction, efficiency of conversion is increased (Karkoodi et al, 2009 In ruminants, niacin is particularly required for protein and energy metabolism, involving liver detoxification of portal blood NH 3 to urea along with metabolism of ketones in liver during ketosis. It is quite evident that niacin can enhance microbial protein synthesis (Girard, 1998).…”
Section: Sourcesmentioning
confidence: 99%